El teatro en el aula como estrategia psicoeducativa para prevenir el acoso escolar en los estudiantes del noveno año de educación básica paralelo a de la escuela 18 de Noviembre, 2019-2020 - Pacheco Ludeña, Maricarmen Soledad (2021)
In the current context, bullying is a behavioral and emotional problem with a negative impact on the mental health of children and adolescents, as well as their academic performance and life aspirations. It is for this reason that the research aimed to implement theater in the classroom as a psychoeducational strategy to prevent bullying in students of the Ninth Year of Basic Education parallel A of the November 18 School. The study was descriptive, with a quasi-experimental cross-sectional design, and the scientific, analytical, synthetic, deductive, inductive methods and the SPSS statistical program were used. The Cisneros Autotest was applied to the sample of 18 students aged 12-15 years. In the pretest results, 38.8% of students showed a high global index of bullying; 50% presented high intensity of harassment and with regard to the levels of harassment by categories, 38.9% were located at a high level, with which it was confirmed that there is bullying; On the other hand, in the post-test, 100% showed a low global index of bullying as well as a low intensity of bullying, and in terms of bullying levels by categories, 96.5% were located at a low level, which showed a very significant decrease in bullying in its different categories. To validate the proposal, the Student's T statistical test was used, where the result of the calculated T value was greater than the tabulated T value, so the alternative hypothesis that dictates that theater in the classroom as a psychoeducational strategy prevents bullying was accepted. . In conclusion, the workshops given with theater activities in the classroom allowed to provide information and strategies for students to develop teamwork skills, respect, empathy and companionship, which led to a better relationship within the classroom avoiding conflicts, it is also recommended To the different actors involved in education, guarantee the student information support spaces to prevent bullying